2017
DOI: 10.1071/fp17054
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of submergence tolerance in rice through efficient application of potassium under submergence-prone rainfed ecology of Indo-Gangetic Plain

Abstract: Potassium (K) is one of the limiting factors that negatively influenced rice growth and yield in submergence-prone soils. We conducted an experiment during the wet season of 2014–15 to achieve optimal doses of K and understand the effect of K application on submerged rice in terms of survival, chlorophyll content, non-structural carbohydrates (NSC), anti-oxidant activities and yield. Results revealed that chlorophyll and NSC content were significantly (P ≤ 0.05) lower whereas the activity of anti-oxidants (cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The simultaneous decrease in nitrate and water circulation from roots to shoots and the increase in root K + efflux tend to induce a potassium deficiency (Phukan, Mishra, & Shukla, 2016). As a matter of fact, waterlogging symptoms have been shown to be partly alleviated by foliar spraying of potassium (Ashraf et al, 2011;Dwivedi et al, 2017;Gautam et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous decrease in nitrate and water circulation from roots to shoots and the increase in root K + efflux tend to induce a potassium deficiency (Phukan, Mishra, & Shukla, 2016). As a matter of fact, waterlogging symptoms have been shown to be partly alleviated by foliar spraying of potassium (Ashraf et al, 2011;Dwivedi et al, 2017;Gautam et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Further, additional fertilization of 20-20 kg N-K 2 O/ha at 5-6 days after termination of submergence was found to be more promising and the most suitable fertilizer rate and application time for better recovery, crop growth, yield, and yield attributes of Swarna Sub1 in the submergence-prone ecosystem. Dwivedi et al (2017) also found that application of potassium at panicle initiation stage was more beneficial to enhance plant survival, better recovery and yield of rice during complete submergence. This might be because potassium mitigates submergence-induced stress in rice by maintaining survival after de-submergence and physiological activities (chlorophyll and antioxidant activity) to mitigate the adverse effect of submergence.…”
Section: Response Of Swarna-sub1 To Post Flood Nutrient Managementmentioning
confidence: 87%
“…In particular, nitrogen has been reported to be the only possible limiting nutrient for rice production in flood-prone areas (Panaullah et al 2001). Similarly potassium application after de-submergence is also considered beneficial especially in submergence prone-areas (Gautam et al 2016b) as it has important role in mitigating submergence-induced stress in rice (Dwivedi et al 2017). Therefore, additional potassium along with N was applied to observe its effect on post submergence recovery.…”
Section: Introductionmentioning
confidence: 99%
“…To date, some studies have focused on problems associated with cultivation, physiology, ecology, genetics, breeding, and other aspects of damage of rice caused by drought (Kumar et al , 2014; Lauteri et al , 2014; Majeed et al , 2013; Hadiarto and Tran, 2011) and flooding (Dwivedi et al , 2017; Winkel et al , 2014; Singh et al , 2014; Gautam et al , 2017). Abrupt drought-flood alternation affects yield and its components, physiological characteristics, matter accumulation and translocation, and rice quality (Zhong et al , 2016; Deng et al , 2017; Xiong et al.…”
Section: Introductionmentioning
confidence: 99%